GAME AS AN ACTIVITY AT THE FOREIGN LANGUAGE LESSON AS ONE OF THE BASIC WAYS OF LEARNING ENGLISH AT PRIMARY SCHOOL - N. Osarova (Galaxy International Interdisciplinary Research Journal, 2022)
Games always play a crucial role in teaching and involves a number of learning tasks. The pressing nature of this issue stems from the need to improve methods of psycho-pedagogical influence on the developing personality of the child in order to foster self-sufficiency in children’s intelligent, communicative, and creative abilities.